My New Business - Kerr, Wendy (Pearson Business, 2014)
Ever wanted to be your own boss? Dreamt of starting your own business but never quite made the leap? For every woman who has ever wondered, "Could I do it?" or been tempted by the idea of managing their own hours and controlling their own destiny, My New Business is the long-awaited answer. Written by someone who's not only "been there, done that"; herself, but who has years of experience helping women just like you take the first steps and start their own businesses, this practical guide gives you the advice, structure and support you need to get it right. It's packed with great time-saving shortcuts, worksheets and savvy advice as well as smart nuggets of wisdom from over 20 female entrepreneurs. So stop dreaming and start doing. Today.